Silencing or inhibition of endoplasmic reticulum aminopeptidase 1 (ERAP1) suppresses free heavy chain expression and Th17 responses in ankylosing spondylitis. Issue 5 (30th June 2015) - Chen, Liye; Ridley, Anna; Hammitzsch, Ariane; Al-Mossawi, Mohammad Hussein; Bunting, Helen; Georgiadis, Dimitris; Chan, Antoni; Kollnberger, Simon; Bowness, Paul
Abstract : Objective: Human leucocyte antigen (HLA)-B27 and endoplasmic reticulum aminopeptidase 1 (ERAP1) are strongly associated with ankylosing spondylitis (AS). ERAP1 is a key aminopeptidase in HLA class I presentation and can potentially alter surface expression of HLA-B27 free heavy chains (FHCs). We studied the effects of ERAP1 silencing/inhibition/variations on HLA-B27 FHC expression and Th17 responses in AS. Methods: Flow cytometry was used to measure surface expression of HLA class I in peripheral blood mononuclear cells (PBMCs) from patients with AS carrying different ERAP1 genotypes (rs2287987, rs30187 and rs27044) and in ERAP1-silenced/inhibited/mutated HLA-B27-expressing antigen presenting cells (APCs). ERAP1-silenced/inhibited APCs were cocultured with KIR3DL2CD3ε-reporter cells or AS CD4+ T cells. Th17 responses of AS CD4+ T cells were measured by interleukin (IL)-17A ELISA and Th17 intracellular cytokine staining. FHC cell surface expression and Th17 responses were also measured in AS PBMCs following ERAP1 inhibition. Results: The AS-protective ERAP1 variants, K528R and Q730E, were associated with reduced surface FHC expression by monocytes from patients with AS and HLA-B27-expressing APCs. ERAP1 silencing or inhibition in APCs downregulated HLA-B27 FHC surface expression, reduced IL-2 production by KIR3DL2CD3ε-reporter cells and suppressed the Th17 expansion and IL-17A secretion by AS CD4+ T cells. ERAP1 inhibition of AS PBMCs reduced HLA class I FHC surface expression by monocytes and B cells, and suppressed Th17 expansion. Conclusions: ERAP1 activity determines surface expression of HLA-B27 FHCs and potentially promotes Th17 responses in AS through binding of HLA-B27 FHCs to KIR3DL2. Our data suggest that ERAP1 inhibition has potential for AS treatment.